Invited Commentary: Examining Sex/Gender Differences in Risk of Alzheimer Disease and Related Dementias—Challenges and Future Directions - Mayeda, Elizabeth Rose (Am J Epidemiol, 2019)
The majority of people living with Alzheimer disease (AD) and related dementias are women. Longer life expectancy is one factor thought to contribute to this observation, but possible sex-specific biological mechanisms have received considerable attention from the research community. In the current issue of the Journal, Buckley et al. (Am J Epidemiol. 2019;188(7):1213–1223) use death certificate information on all deaths occurring among adults aged ≥60 years in Australia between 2006 and 2014 to evaluate sex/gender differences in rates of death with dementia (all types), AD dementia, and vascular dementia listed on the death certificate. The paper by Buckley et al. highlights several important methodological challenges for research examining sex/gender differences in risk of AD and related dementias, including challenges in measurement, survival bias and competing risks, and selection bias arising from sample selection. The current evidence on possible sex-specific biological risk factors for AD is intriguing, but there are numerous alternative explanations for differences in AD dementia and AD biomarkers between women and men. Triangulation of evidence from study designs with different strengths and weaknesses and transdisciplinary collaboration will be vital to generating conclusive evidence about sex/gender differences in risk of AD and related dementias.